Aortic Arch Calcification Is a Strong Predictor of the Severity of Coronary Artery Disease in Patients with Acute Coronary Syndrome. (7th August 2019) - Ma, Xiaoteng; Hou, Fangjie; Tian, Jing; Zhou, Zhen; Ma, Yue; Cheng, Yujing; Du, Yu; Shen, Hua; Hu, Bin; Wang, Zhijian; Liu, Yuyang; Zhao, Yingxin; et al.
Abstract : Background . The purpose of this study was to investigate the correlation of the extent of aortic arch calcification (AAC) detectable on chest X-rays with the severity of coronary artery disease (CAD) as evaluated by the SYNTAX score (SS) in patients with acute coronary syndrome (ACS). Methods. A total of 1, 418 patients (344 women; 59 ± 10 years) who underwent coronary angiography for ACS and were treated with coronary revascularization were included in the present study; chest X-rays were performed on admission. The AAC extent was divided into four grades (0–3). SS was calculated based on each patient's coronary angiographic findings. The relationship between the AAC extent and SS was assessed. Results . The AAC extent was positively correlated with SS ( ρ = 0.639, P < 0.001). In the multivariate analysis, compared with grade 0, odds ratios (ORs) of AAC grades 1, 2, and 3 in predicting SS >22 were 12.95 (95% CI, 7.85–21.36), 191.76 (95% CI, 103.17–356.43), and 527.81 (95% CI, 198.24–1405.28), respectively. Receiver operating characteristic curve analysis yielded a strong predictive ability of the AAC extent for SS >22 (area under curve = 0.840, P < 0.001). Absence of AAC had a sensitivity, specificity, positive prognostic value, negative prognostic value, and accuracy of 46.7%, 95.9%, 94.1%, 56.4%, and 67.3%, respectively, for SS ≤22. AAC grades ≥2 had a sensitivity of 66.3%, specificity of 89.2%, positive prognostic value of 81.5%, negative prognostic value of 78.6%, and accuracy of 79.6% for the correct identification of SS >22. Conclusions . The extent of AAC detectable on chest X-rays might provide valuable information in predicting CAD severity in ACS patients.